To Save Whom They Can: Another Look at Philo and Missionary Deceit - Macdonald, A. D. (New Testament studies, 2020)
Henry Chadwick proposed in the 1960s that Philo's Questions and Answers in Genesis 4.69 is important for understanding Paul's mission strategy in 1 Cor 9. In 2011 David J. Rudolph revisited that ‘missionary-apologetic’ reading of QG 4.69 in a discussion of Paul's observance of the Torah but refrained from drawing firm conclusions. This article subjects the missionary-apologetic hypothesis to closer scrutiny, especially regarding its plausibility as a reading of Philo. It argues that Chadwick's hypothesis lacks both evidence and explanatory power. QG 4.69, therefore, contributes little to our understanding of 1 Cor 9 and of Paul's missionary strategy and Torah observance.